Inovasi dan Empowerment Kelompok Tani Untuk Meningkatkan Pengelolaan Food Security di Desa Tanjung Morawa A - Muhammad Ardian; Indra Kesuma Nasution; Fernanda Putra Adela; Ira Rizka Aisyah Lubis; Sri Rahayu Sanusi; Suhendri (PELITA NUSA TENGGARA, 2026)
Food security is also a national strategic issue that has become a key focus in sustainable development, particularly in the agricultural and rural sectors. This program aims to enhance the capacity and quality of farmer groups in Tanjung Morawa A Village, Tanjung Morawa Sub-district, Deli Serdang Regency, in supporting village food security initiatives aligned with national priorities. The approach is carried out through training based on dialogue, interactive discussions, and hands-on practice. Farmer groups were equipped with practical knowledge and strategies to overcome challenges in seed cultivation and the management of both agricultural and livestock sectors. One of the approaches introduced was the Kaizen method from Japan, which emphasizes continuous improvement based on participation and root-cause problem solving. This activity demonstrated that appropriate innovation and empowerment can effectively promote the active involvement of rural communities in realizing sustainable food security. As a result, participants showed increased understanding and motivation to commit to food security programs. This initiative marks the beginning of strengthening a community-based village food system that is adaptive, innovative, and self-reliant.